The Role of Internal Audit Quality to the Sustainability and Success of Microfinance Program - Saikou Gassama; Erina Sudaryati (Manajemen Bisnis, 2022)
Microfinance institutions are the main source of finance for the poor and the women in many country, therefore the sustainability of these companies is a concern, but that cannot be achieved without proper internal control mechanism to detect any attempt frauds that could harm the operations of microfinance institutions. The research will used literature review method by digging into previous researches to see the main courses of the failure of many microfinance institutions. The research found out that most of the microfinance institution failed due to inadequate control in place to detect malfunctions or fraud at the earlier stages that can safeguard the operations of microfinance institutions.